Vagueness and Exactiveness in class II, division 2 diagnostics - P. Jindra (Czech Dental Chamber, 2020)
Introduction, aim: Class II division 2 malocclusion is usually defined by natural informal language (czech, english etc.) as a combination of deep bite and upper central incisor retrusion. There are borderline cases of deep bite and incisor retrusion, which cause doubts about class II division 2 diagnostics. The existence of borderline cases is a sign of vague definition of examined phenomenon.The goal of presented article is to analyze concepts of vagueness and exactiveness in class II division 2 diagnostics. A quantity distance and a quantity angle will be analyzed, which enable mathematization of class II division 2 diagnostics. Opinion piece and conclusion: The description of real world around us and of orofacial systems of our patients by means of quantities is a method of exact sciences. The article analyzes the difference between vagueness and exactiveness during class II division 2 diagnostics. In dentistry we use both filters of real world complexity. We use vagueness as we talk and write about dentistry phenomena using natural informal language. But we use tools of exactiveness as well as we introduce quantities in a suitable way and we describe phenomena by quantities and their relations.